2007
DOI: 10.1002/pts.788
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of model compounds–polypropylene film interactions by Fourier transformed infrared spectroscopy (FTIR) method

Abstract: The interactions of methyl esters, methyl ketones and aldehyde compounds with polypropylene (PP) film were investigated. PP film, placed on a glass vial, was immersed in aqueous solution containing a model flavour compound. After a determined time at 45°C, the PP film was analysed by Fourier transform infrared spectroscopy (FTIR), allowing us to follow the speed of sorption and to quantify its relative rate.For PP films, we observed that the sorption strongly depended on the structure of sorbed molecules. For … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 30 publications
(30 reference statements)
0
8
0
Order By: Relevance
“…In the case of 2‐hexanal, its sorption by LDPE increased by a factor of 40 when the pH of the solution increased from 3 to 5. Lowering the pH to 3 increased the sorption of alcohols into LDPE . There is no significant change in the sorption of aldehydes, esters and alcohols in LDPE by the addition of a few drops of acetic acid in the flavoured aqueous solution .…”
Section: Factors Affecting Sorption Processes In Package–product Systemsmentioning
confidence: 92%
See 3 more Smart Citations
“…In the case of 2‐hexanal, its sorption by LDPE increased by a factor of 40 when the pH of the solution increased from 3 to 5. Lowering the pH to 3 increased the sorption of alcohols into LDPE . There is no significant change in the sorption of aldehydes, esters and alcohols in LDPE by the addition of a few drops of acetic acid in the flavoured aqueous solution .…”
Section: Factors Affecting Sorption Processes In Package–product Systemsmentioning
confidence: 92%
“…Safa et al also observed that for the linear components and comparable mass the linear components and comparable mass, the sorption kinetic is appreciably the same, but the rate of sorption equilibrium varied according to the following order: ester > ketone > aldehyde . Ketones and aldehydes required a much shorter time, approximately 5 h, to reach equilibrium in comparison with esters which required 15–20 h. The sorption curves for ester groups indicated a high affinity of dodecyl acetate to PP film …”
Section: Factors Affecting Sorption Processes In Package–product Systemsmentioning
confidence: 93%
See 2 more Smart Citations
“…Owing to its hydrocarbon structure, especially the presence of a tertiary Tensile properties of polypropylene fibres [22,38] C-H bond, PP is relatively sensitive to thermal and photochemical oxidation. It cannot be processed, stored or used without stabilizers [44].…”
Section: Polypropylene (Pp) Structure and Propertiesmentioning
confidence: 99%